“Cueing” for Levodopa-Induced Dyskinesias in Parkinson’s Disease - Schaeffer, Eva; Linke, Gerd; Berg, Daniela (Frontiers in Neurology, 2016)
We describe the case of a an early onset Parkinson’s disease (PD) patient, suffering from a severe and unusual dyskinetic gait pattern, earlier described as „Silly walk“. On presentation, the 58 year old patient showed a painful, bizarre dyskinetic gait disorder, resulting in a significantly impairment of her social life. We developed an individual conservative training method for the patient, using „Cueing mechanisms“, well known for treatment of Freezing in PD, to overcome her dyskinetic gait pattern. An impressive improvement was seen after the use of visual and acousting cues. We therefore conclude that it might be important for PD patients to recognize these specific movement abnormalities and start early with individualized training methods. Moreover especially for „Silly walks“ individual „Cueing“ strategies can be an important new basis of conservative trainings methods for dyskinesia.